PENGAWASAN PEREDARAN ROKOK TANPA PITA CUKAI OLEH BIDANG PENINDAKAN DAN PENYIDIKAN DI KPPBC TIPE MADYA PABEAN A SEMARANG - Perkasa, Ronald Arya Bayu; Mulyani, Tri; Pujiastuti, Endah (Fakultas Hukum, Universitas Semarang, 2024)
Excise as government revenue from the object of the Directorate General of Customs and Excise results from the excise sector including the results of tobacco derivative products such as cigarettes are regulated in Law Number 39 of 2007 concerning Excise. Excise tape in the form of a state security document as a sign that the cigarette has paid its excise. The role of the P2 field in the implementation in the field of customs prosecution and investigation of the results of supervision carried out to prevent the circulation of cigarettes without excise tapes at the Customs and Excise Supervision and Service Office of Customs Type A Semarang. The research methods used include, type of sociological juridical research, research specifications are descriptive analytical Data used are primary data and supported by secondary data, with qualitative data analysis. The results showed that the supervision of cigarettes without excise tax bands carried out by section P2 at KPPBC Type Madya Pabean A Semarang through 3 supervision methods namely Compliance Tests, Partnership Supervision, and Information Media in 6 cities and regencies in the KPPBC Type Madya Pabean A Semarang area. The existence of constraints by legal and cultural factors on the regulation of the effect of increasing excise tax on the honesty of perpetrators in distributing cigarettes without excise tax. Enforcement of this obstacle is carried out with preventive efforts and constraints on the location of the KPPBC area Type Madya Pabean A Semarang in monitoring the circulation of cigarettes without excise tax. Because the location of the Semarang City area has toll road access as a route to the city of Semarang. The existence of constraints by legal and cultural factors on the regulation of the effect of increasing excise tax on the honesty of perpetrators in distributing cigarettes without excise tax. Enforcement of this obstacle is carried out with preventive efforts and constraints on the location of the KPPBC area Type Madya Customs A Semarang in monitoring the circulation of cigarettes without excise tax. Because the location of the Semarang City area has toll access as a transportation route with repressive efforts carried out by P2 Intelligence at KPPBC Type Madya Pabean A Semarang. AbstrakCukai sebagai pendapatan pemerintah dari objek hasil Direktorat Jenderal Bea dan Cukai dari sektor cukai termasuk hasil produk turunan dari tembakau seperti rokok diatur dalam Undang-Undang Nomor 39 Tahun 2007 tentang Cukai. Pita Cukai berupa dokumen sekuriti negara sebagai tanda rokok dilunasi cukainya. Peran bidang P2 dalam pelaksanaan di bidang penindakan dan penyidikan kepabeanan hasil pengawasan yang dilakukan mencegah peredaran rokok tanpa pita cukai di Kantor Pengawasan dan Pelayanan Bea dan Cukai Tipe Madya Pabean A Semarang. Metode penelitian yang dipergunakan diantaranya, jenis penelitian yuridis sosiologis, spesifikasi penelitian adalah deskriptif analitis Data yang dipergunakan adalah data primer dan didukung dengan data sekunder, dengan analisis data kualitatif. Hasil penelitian menunjukkan bahwa pengawasan rokok tanpa pita cukai yang dilakukan oleh seksi P2 di KPPBC Tipe Madya Pabean A Semarang melalui 3 metode pengawasan yakni Uji Kepatuhan, Pengawasan Kemitraan, dan Media Informasi pada 6 Kota dan Kabupaten kawasan wilayah KPPBC Tipe Madya Pabean A Semarang. Adanya kendala oleh faktor penetapan hukum dan budaya terhadap regulasi pengaruh peningkatan cukai terhadap kejujuran pelaku dalam pengedarkan rokok tanpa pita cukai. Penindakan kendala ini dilakukan dengan upaya preventif dan kendala pada letak wilayah KPPBC Tipe Madya Pabean A Semarang dalam pengawasan peredaran rokok tanpa pita cukai. Sebab letak wilayah Kota Semarang memiliki akses tol sebagai jalur transportasi dengan upaya represif yang dilakukan oleh Intelejen P2 di KPPBC Tipe Madya Pabean A Semarang.